Quedancor pro-farmer focus profiles of the farmer beneficiaries of the Barangay Marketing Center Program. - Quedan and Rural Credit Guarantee Corporation ([S.l.] Produced by the Promotions and Publications, 1996)
Contents: CBMC profiles. FLGC profiles. Programs primer. Map of CBMCs/FLGCs in the countryside.
Purpose: A publication presenting the 84 farmer cooperative beneficiaries of the Quedan and Rural Credit Guarantee Corporation's (Quedancor) CARP Barangay Marketing Center (CBMC) and Farm Level Grains Center (FLGC) projects. Each of the 71 CBMCs and 13 FLGCs have a two-page profile containing details such as credit assistance, cooperative profile, founding date, and present activities. In the back is a programs primer describing the requirements and incentives provided in the above programs, as well as a map showing the distribution of CBMCs and FLGCs all over the country.
Cover title.
Keywords: Agricultural cooperative credit associations -- Philippines -- Directories; Agriculture, Cooperative -- Philippines